(untitled) (Revista Contexto & Saúde, 2023)
Anemia affects almost a quarter of the world’s population and causes numerous damages to various tissues, causing low oxygenation and signs and symptoms such as shortness of breath, lack of appetite, headache, dizziness and learning disabilities. However, there are no data on anemia in children in northern Brazil, which is necessary to establish reliable parameters for reestablishing the health of these patients. Our objective was to evaluate cases of anemia reported in children in the northern region of Brazil.This are a retrospective cross-sectional study, carried out over a period of one year. Demographic characteristics were noted, all children were carefully assigned to the study. The blood collection procedure was performed according to the established protocol. A total of 600 patients were included in the study. Most were female (52.5%), brown (51.6%), with a family income of 1 to 2 minimum wages and incomplete primary education. Anemia was more evident in ages 9 to 12 years (74.8%) and the proportion of children with hematocrit, iron, and ferritin below 35%, 50 µg/dL and 7 µg/L, respectively, was higher among children’s patients with anemia. In addition, they had numerous morphological classification variables, compared to the hemametric index. The study showed that anemia affects children. In view of the magnitude of the risks presented in this article, preventive measures for this pathology must be implemented to guarantee the integrity of the health of these patients, under penalty of irreversible damage for future generations.